PENYELESAIAN WANPRESTASI DALAM PERJANJIAN JUAL BELI ALAT BERAT ANTARA PT DAYA KOBELCO DAN PT CATUR BATAVIA TRASINDO (STUDI PUTUSAN NO.394 PDT.G/2018/PN - Jihan Nazira Ardian, (2021)
A breach of contract is the implementation of an obligation that is not on time or done inappropriately and it creates an obligation for the debtor to provide or pay compensation. The problems discussed in this study are how the form of breach occurs in the heavy equipment sale and purchase agreement between PT Daya Kobelco and PT Catur Batavia Transindo and how to resolve breaches related to Decision No.394 Pdt.G/2018/PN Bks. This study aims to determine the form of the breach in the haevy equipment sale and purchase and determine the legal settlement of the breach by PT Catur Batavia Trasindo. This type of research is normative juridical research. The method of data collection is techniques library research carried out by collecting secondary data. Based on the research results, the form of the breach in the sale and purchase agreement was to do what was promised, but not as promised. The legal settlement of breach is through a court conducted at the Pengadilan Bekasi because PT Catur Batavia Transindo was not in good faith to PT Daya Kobelco, which had sent subpoena twice. The trial results determined that PT Catur Batavia Transindo was proven to have breached and was sentenced to pay all obligations for the remaining debt to purchase the unit to PT Batavia Transindo along with the fine.